1988
DOI: 10.1002/ijc.2910420608
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical distribution of c‐erbB‐2 in infiltrating and in situ breast cancer

Abstract: An immunohistochemical study of c-erbB-2 expression was performed on invasive and in situ breast cancer. Strong membrane staining was seen in 16% of the infiltrating ductal carcinomas and 44% of the in situ lesions. c-erbB-2 was overexpressed in ductal rather than lobular tumours. Our results indicate that a small sub-group of breast carcinomas are associated with over-expression of this oncogene which may define an important subgroup of in situ and infiltrating ductal carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
47
0
2

Year Published

1991
1991
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(50 citation statements)
references
References 12 publications
1
47
0
2
Order By: Relevance
“…Others have not observed a statistically significant relationship in breast cancer (Gusterson et al, 1988;Ali et al, 1988;Zhou et al, 1989;Barnes et al, 1988) although a trend has been observed. In two reports c-erbB-2 overexpression could not be demonstrated to be associated with poor prognosis in node negative breast cancer patients, where it would be potentially of most value clinically (Slamon et al, 1989;Tandon et al, 1989).…”
mentioning
confidence: 95%
“…Others have not observed a statistically significant relationship in breast cancer (Gusterson et al, 1988;Ali et al, 1988;Zhou et al, 1989;Barnes et al, 1988) although a trend has been observed. In two reports c-erbB-2 overexpression could not be demonstrated to be associated with poor prognosis in node negative breast cancer patients, where it would be potentially of most value clinically (Slamon et al, 1989;Tandon et al, 1989).…”
mentioning
confidence: 95%
“…This antibody, which is a rat IgG2a monoclonal, is directed against the extracellular domain of the 185 kDa product of the c-erbB-2 proto-oncogene; a transmembrane tyrosine kinase related to the receptor for epidermal growth factor. Amplification of this gene and overexpression of the product has been found in some 20% of breast cancers and overexpression has been found to correlate with poor prognosis in these patients (Slamon et al, 1987;Gusterson et al, 1988). The minimal levels of expression of this antigen in most normal tissues make this a highly tumour specific target (Perren, 1992).…”
mentioning
confidence: 99%
“…Three of these papers are particularly notable: two because they are amongst the largest systematically collected series in the literature reporting data on 497 and 462 patients respectively (Lovekin et al, 1991;Winstanley et al, 1991); the third paper (Gullick et al, 1991) is notable because it reports the results of a form of metaanalysis which combines the results of three relatively small previously published studies (Gusterson et al, 1988;Barnes et al, 1988;Wright et al, 1989a) to produce a much more statistically robust conclusion than could be derived from any one of the studies alone. The fourth papers reports the results of a moderately sized study (172 patients) and is interesting because in addition to reporting the association between c-erbB-2 expression and conventional prognostic factors it also examines the association of its expression with S-phase fraction as a marker of tumour proliferation as measured by DNA flow cytometry (O'Reilly et al, 1991).…”
mentioning
confidence: 99%
“…The original study reported by Slamon et al (1987) showed a positive association between c-erbB-2 expression and the number of involved axillary nodes, this finding has not been generally reproducible but finds some support in three other studies (Tandon et al, 1989;Guerin et al, 1989;May et al, 1990) and indirectly in the study by Zhou et al (1989) ship between c-erbB-2 expression and other markers of differentiation. Ploidy has previously been investigated by two groups neither of whom found any significant association (Tavassoli et al, 1989;Ro et al, 1989) At least 20 other groups have now published data concerning the prognostic significance of c-erbB-2, of these only four groups have failed to find a prognostic effect of c-erbB-2 in at least one sub group (Zhou et al, 1989;Ali et al, 1988;Gusterson et al, 1988;Barnes et al, 1988). Van 1990;Walker et al, 1989;Tsuda et al, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation